2019 IEEE International Conference on Artificial Intelligence and Virtual Reality (AIVR) 2019
DOI: 10.1109/aivr46125.2019.00040
|View full text |Cite
|
Sign up to set email alerts
|

Towards Method Time Measurement Identification Using Virtual Reality and Gesture Recognition

Abstract: Methods-Time Measurement (MTM) is a predetermined motion time system that is used primarily in industrial settings to analyze the methods used to perform any manual operation. In this paper, we introduce a system for automatic generation of MTM codes using only head and both hands 3D tracking. Our approach relies on the division of gestures into small elementary movements. Then, we built a decision tree to aggregate these elementary movements in order to generate the realized MTM code. The proposed system does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This potential time saving through automated transcription can be considered as a rough estimate for the actual savings potential. Therefore, our study can also be seen as a proof of concept for a fully automated MTM analysis, which was proposed by Bellarbi et al [2].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This potential time saving through automated transcription can be considered as a rough estimate for the actual savings potential. Therefore, our study can also be seen as a proof of concept for a fully automated MTM analysis, which was proposed by Bellarbi et al [2].…”
Section: Discussionmentioning
confidence: 63%
“…It was reported that the hand tracking often fails to correctly locate the hands if illumination conditions vary. A tree-based approach to recognize MTM-UAS codes in VR was proposed by Bellarbi et al [2]. It captures the tracking data of an HMD and controllers and divides this data into small sequences of movements.…”
Section: Related Workmentioning
confidence: 99%
“…Oppositely, the investigations carried out by [4,38], validate their goals with the MTM methodology using simulated study cases in controlled environments, in which using digital applications studied manual activities. The two articles use the methodology correctly , but in the last one, the activities do not add value to the process causing the estimated time not approximately to the real industry process.…”
Section: Rq2: What Are the Work Measurement Techniques Used In Theses Times?mentioning
confidence: 91%
“…The aforementioned algorithm from Bellarbi et al [15] works on data that were recorded during a virtual MTM session. However, this comes to the cost of recording a vast amount of data, which actually prohibits analyzing longer work sequences.…”
Section: Algorithm Developmentmentioning
confidence: 99%
“…Only little work can be found specifically on the topic of automatic MTM transcription for industrial applications. The first work is from Bellarbi et al [15], in which an algorithm was developed to automatically generate MTM-UAS codes. The proposed algorithm follows a decision tree-like structure, where all the MTM basic motions are classified in groups, among which are "eye movement", "hand movement", and "body movement".…”
Section: Related Workmentioning
confidence: 99%